Effects of inclusive leadership on organizational citizenship behavior: the mediating roles of organizational justice and learning culture. (2019) - Hanh Tran, Thi Bich; Choi, Suk Bong
Abstract: The aim of this article is to examine the causal relationship between inclusive leadership and employees' organizational citizenship behavior (OCB) of Vietnam service workers. This article also examines the mediating roles of organizational justice and organizational learning culture in this causal relationship. We collected data via a questionnaire survey of a sample of 268 employees from four service firms in Vietnam. The results showed that inclusive leadership is positively related to OCB. Moreover, both organizational justice and organizational learning culture played partial mediating roles in the inclusive leadership–OCB relationship. The findings advance the literature on leadership by studying an underexplored type of leadership in relation to employee OCB. They also extend our knowledge of organizational justice and learning culture by specifying these as mediators in the mechanisms of employee inclusive leadership–OCB relations. The article thus adds to a body of work in which OCB is connected with leaders' behavior and organizational level predictors.